Artikel Kilit Kalut: Teater Pakeliran sebagai Representasi Konflik Batin Tokoh Salya: Kilit Kalut: Teater Pakeliran sebagai Representasi Konflik Batin Tokoh Salya - Wahyu Widiyantara, I Komang; Sidia, I Made; Widnyana, I Kadek; Akbar, Hanolda Gema (Pusat Penerbitan LP2MPP ISI Bali, 2026)
The creation of the puppetry performance Kilit Kalut is grounded in the need to expand the aesthetic and social functions of Balinese puppetry in responding to contemporary human inner conflicts. Traditional puppetry has predominantly emphasized external conflicts, leaving psychological dimensions underexplored. This study aims to represent the inner conflict of Salya from the Kakawin Baratayudha through a teater pakeliran framework as an artistic innovation. A qualitative-descriptive method with a practice-based research approach was employed, utilizing Harymawan’s 4M stages (imagining, writing, performing, observing), supported by rehearsal observations, textual analysis, and cross-media artistic exploration. The results demonstrate that the integration of Balinese shadow puppetry, live actors, lighting design, and gamelan effectively constructs a symbolic and dramatic representation of psychological duality. This innovation repositions puppetry as a medium for existential reflection rather than mere entertainment or ritual performance. This study introduces inner conflict as the central dramaturgical axis in Balinese puppetry through an integrative teater pakeliran approach. In conclusion, the study contributes to the development of contemporary puppetry aesthetics while sustaining traditional values within a modern cultural context.